Simulation Analysis and Experimental Testing of Spin-Magnetic Piezoelectric Generators - Xiaochao Tian; Hu Wang; Jiaying Lin; Zhicong Wang; Jinlong Liu; Shenfang Li; Jun Hou; Jinzhi Zhu; Qing Lei (Advances in Materials Science and Engineering, 2022)
In order to investigate the optimal power generation performance of piezoelectric materials, a spin-magnetic piezoelectric generator was designed and the relationship between output voltage and speed and external force was derived through theoretical analysis. The maximum deformation and resonant frequency of the piezoelectric oscillator under magnetic drive are derived from simulation analysis. Finally, the relationship between output voltage and magnet size, distance between two magnets, and speed was tested experimentally, and the experimental data agreed with the theoretical analysis. The results show that when the speed is 312 r/min, magnet pitch is 12 mm, and magnet size is 10 mm  ∗ 35 mm∗ 4, the maximum output voltage is 54 V. This can meet the power supply needs of micro and small electronic products.